Simulation of free-electron lasers seeded with broadband radiation - Bajlekov, S; Fawley, WM; Schroeder, C; Bartolini, R; Hooker, S (2011)
The longitudinal coherence of free-electron laser (FEL) radiation can be enhanced by seeding the FEL with high harmonics of an optical laser pulse. The radiation produced by high-harmonic generation (HHG), however, has a fast-varying temporal profile that can violate the slowly varying envelope approximation and limited frequency window that is employed in conventional free-electron laser simulation codes. Here we investigate the implications of violating this approximation on the accuracy of simulations. On the basis of both analytical considerations and 1D numerical studies, it is concluded that, for most realistic scenarios, conventional FEL codes are capable of accurately simulating the FEL process even when the seed radiation violates the slowly varying envelope approximation. We additionally discuss the significance of filtering the harmonic content of broadband HHG seeds. © 2011 American Physical Society.